The Role of Government in the Housing Market - Laskowska, Elwira; Torgomyan, Sevak (Zeszyty Naukowe SGGW w Warszawie - Problemy Rolnictwa Światowego, 2016)
Nowadays one of the most intensely debated subjects in economics is government intervention in real estate market. Proponents of the free market system assert that government intervention should be strongly limited still others assert there are well-grounded reasons for government intervention. In this article the most common methods and forms of government intervention in real estate market such as legislation, subsidies, taxation, zoning, rent control, minimum and maximum price policies, licensing of market participants, transaction costs and procedures, banking system, restrictions on the involvement of financial institutions in real estate market have been observed. In practice, each government uses these intervention methods with the choice of method depending on factors such as the political slant of the government, the levels of economic and institutional development, et cetera. Some countries even issue residence permit and citizenship foreigners who invest in the housing market. We find government intervention necessary, given the unique characteristics of real estate and the role that it plays in economic and social progress.